Design and Build Animated Procedures for Praying in Mosques During a Pandemic - Rian Septiawan; Cindy Taurusta (Universitas Muhammadiyah Sidoarjo, 2021)
The world is currently shocked by the presence of a new type of outbreak, namely the Corona virus, which has now troubled human health, an educational animation has been made so that it can convey health protocol information to be conveyed to the public in a more interesting way. This research method using observation is a data collection by observing mosque visitors who often ignore health protocols. The results of this study indicate the importance of implementing health protocols and procedures for carrying out health protocols, especially for mosque congregants who will pray.